Piperine improves ischemic brain injury by promoting the regulation of the AMPK/PGC-1α pathway by Apelin 13 - Xi, Siyu; Ma, Jiangbo; Yan, Jing; Li, Yanzhong; Zhang, Peng; Chen, Huiling; Yang, Guangyu; Fu, Xueyan; Liu, Juan; Zhang, Yiwei (Frontiers in Pharmacology, 2026)
BackgroundIschemic stroke (IS) persists as the second foremost cause of mortality and the primary cause of long-term disability globally, a burden largely attributable to a paucity of effective therapeutic strategies. Piperine (PIP) is a bioactive component of traditional Chinese medicine that has shown potential to reduce cell inflammation and pyroptosis. Recent studies indicate that mitochondrial biogenesis can improve ischemic stroke.ObjectiveIn this study, we aimed to investigate the effect of PIP combined with Apelin 13 on mitochondrial biosynthesis in IS and determine its mechanism and whether PIP promotes Apelin 13.MethodsWe used network pharmacology to screen chemical drugs for combination therapy for IS. Male Sprague–Dawley rats were utilized to induce a model of pMCAO, and primary cortical neuron cells were extracted to establish an oxygen–sugar deprivation–reperfusion model. To evaluate the changes in mitochondrial function of neuronal cells, we observed mitochondrial membrane potential via fluorescence microscopy, detected ROS levels by flow cytometry, and determined the ATP concentration by using a chemiluminescence multifunctional microplate reader. Western blot and qRT-PCR were used to detect the protein expression and mRNA content of Apelin 13 and the AMPK/PGC-1α pathway. In addition, the underlying mechanism of action of PIP promoting Apelin 13 in the regulation of the AMPK/PGC-1α pathway by using siRNA to reduce the content of Apelin 13 in primary cortical neurons was investigated.ResultsThe results of network pharmacology research indicated that Apelin 13 affects IS. PIP combined with Apelin 13 exerts neuroprotective effects against IS. The OGD/R group showed obvious mitochondrial functional damage, reduced mitochondrial membrane potential, increased reactive oxygen species level, and decreased ATP content compared with the Con group. Compared with the OGD/R group, the mitochondrial function detection and expression level of mitochondrial biogenesis-related factors in the PIP and Apelin 13 groups significantly improved, and the neuroprotective effect was more significant when the two were combined. Our in vitro and in vivo experiments revealed that, compared with the normal group, the mRNA and protein expression of Apelin 13 in the model group significantly decreased. Furthermore, the abundance of Apelin 13 in the PIP group substantially rose compared with that in the model group. When the expression of Apelin 13 was knocked down by si-Apelin 13, si-Apelin 13 effectively blocked the individual or even combined effects of PIP and Apelin 13.ConclusionThis study showed that PIP could promote Apelin 13 to activate mitochondrial biogenesis and decreased mitochondrial functional damage. The potential mechanism of activating mitochondrial biogenesis lies in the regulation of the AMPK/PGC-1α pathway. This study not only expands the understanding of the clinical application of PIP in the treatment of IS but also provides new insights into its internal mechanism.